Dental Ceramics: Fracture Mechanics and Engineering Design - Lohbauer, Ulrich; Belli, Renan (Springer International Publishing, 2022)
This book is an evidence-based update on recent most significant advances in dental ceramics, specifically related to the relationships between composition, microstructure and mechanical behavior. Readers will find an introduction to the chemistry of dental ceramics as well as information about the technological progress and practical requirements restorative materials need to satisfy for long-lasting structural integrity. The book uses mechanistic approaches to address failure mechanisms from controlled experiments thus providing the tools for the application of sound research methodologies in the field. It is targeted for researcher and dentists interested in the field of dental ceramic materials and fracture mechanics.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Brittle failure; Dental ceramics; Long-lasting dental esthetics; Microstrucutre of dental ceramics; Restorative dental materials